Individualism: A Work of Musical Composition Experimental | Individualisme : Sebuah Karya Musik Eksperimental - Ida Bagus Oka Prabawa; Ni Putu Hartini (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
This experimental musical work entitled Individualism aims to convey the nature of humans who have an excessive understanding of idealism. Reveal about how they live a life that is analogous to their own beliefs. Starting from their idealistic attitude, the characteristics of those who tend to want to be alone, want to have their own freedom, fulfill their needs, run their own lives, and sometimes they will do anything to achieve satisfaction. This individualism attitude is not from individually, sometimes also in groups that will unite their perceptions under the control of someone as the leader. The creation of this musical composition uses the creation method of Alma H. Hawkins in the book Method of Compiling Musical Works (An Alternative) by Pande Made Sukerta (Sukerta, 2011). The stages or methods in question are exploration, casting and experimentation (improvisation), and forming. From these stages or methods, the stylist carries out a creative process, a concept of the nature of individualism which started from an idea that led to the use of instruments and also to the pattern of working on a work. From this work, we can reflect for our survival so that in the future it will not be a disappointment and regret for ourselves and others. This work is poured into an instrument that has its own rhythm, timbre, and dynamics, which illustrates the attitude of each idealist.